1994
DOI: 10.1021/bi00199a040
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Glycerol Kinase: Role of a Tetramer Interface in Regulation by Fructose 1,6-Bisphosphate and Phosphotransferase System Regulatory Protein IIIglc

Abstract: Escherichia coli glycerol kinase (EC 2.7.1.30; ATP:glycerol 3-phosphotransferase) is a key element in a signal transduction pathway that couples expression of genes required for glycerol metabolism to the relative availability of glycerol and glucose. Its catalytic activity is inhibited by protein-protein interactions with IIIglc, a phosphotransferase system protein, and by fructose 1,6-bisphosphate (FBP); each of these allosteric effectors constitutes a positive signal that glucose is available. Loss of gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 23 publications
5
63
0
Order By: Relevance
“…Surprisingly, two of the alternate alleles (A218T and G217T) affected the same amino acid (Asp73) as the A218T mutation in clone GB-1. A mutation in this amino acid was identified in a previous study 25 and was shown to decrease inhibition by FBP and the formation of inactive tetramers. For the A218T mutation in GD, we were able to rule out cross-contamination because the accompanying rpoC mutation from GB was not present in GD colonies.…”
Section: Mutation Frequencies In Evolving Populationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Surprisingly, two of the alternate alleles (A218T and G217T) affected the same amino acid (Asp73) as the A218T mutation in clone GB-1. A mutation in this amino acid was identified in a previous study 25 and was shown to decrease inhibition by FBP and the formation of inactive tetramers. For the A218T mutation in GD, we were able to rule out cross-contamination because the accompanying rpoC mutation from GB was not present in GD colonies.…”
Section: Mutation Frequencies In Evolving Populationsmentioning
confidence: 88%
“…Every day, optical density (OD) measurements were made and cells were diluted into fresh medium, estimating the amount of inoculum to use such that the culture would not enter stationary phase. Samples were frozen at days 2,4,6,8,10,15,20,25,30,35, 40 and 44.…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli strain MV1190 or DG1 [37] was transformed with an expression vector, pT3-5LO, which contains a human 5LO cDNA insert [38]. An overnight culture was grown at 30 mC in Luria-Bertani medium containing 150 µg\ml ampicillin.…”
Section: Preparation Of 5lomentioning
confidence: 99%
“…1C). In solution, EcGK shows an equilibrium between homodimers and homotetramers (18), and FBP inhibition requires tetramer formation (19). Sedimentation velocity ultracentrifugation shows that HiGK sediments more slowly than EcGK in the absence of FBP, suggesting the presence of a greater fraction of dimer but about the same as EcGK in the presence of FBP.…”
mentioning
confidence: 97%
“…Allosteric inhibition of EcGK by FBP and IIA Glc operate independently, and IIA Glc inhibition does not require tetramer formation (19)(20)(21). Thus, HiGK is naive with respect to allosteric control by E. coli IIA Glc .…”
mentioning
confidence: 99%